New Business Activity and Employment Dynamics in the Inner City: The Case of Phoenix, Arizona. Issue 2 (March 2019) - Mack, Elizabeth A.; Credit, Kevin
Inner city revitalization efforts centered on fostering new business activity are controversial because they assume that the job creating capacity of new businesses is capable of impacting aggregate employment levels in inner city neighborhoods. Given this controversy, this article examines the link between new business activity and inner city employment growth in Phoenix, Arizona. Analytical results highlight job creation from new business activity but a net negative association between new business activity and employment growth stemming from the loss of jobs from large employers in inner city neighborhoods. This relationship highlights that encouraging new business activity is not necessarily a bad idea for local residents and customers, but should not be viewed as a panacea for all inner city problems. Instead, new business activity should be viewed as one component of multifaceted initiatives to revitalize inner city neighborhoods.